Traumatic Brain Injury Imaging in the Second Near‐Infrared Window with a Molecular Fluorophore. Issue 32 (2nd June 2016) - Zhang, Xiao‐Dong; Wang, Huasen; Antaris, Alexander L.; Li, Lulin; Diao, Shuo; Ma, Rui; Nguyen, Andy; Hong, Guosong; Ma, Zhuoran; Wang, Joy; Zhu, Shoujun; Castellano, Joseph M.; et al.
Abstract : Traumatic brain injury (TBI) is a leading cause of death and disability worldwide. A bright, renal‐excreted, and biocompatible near‐infrared II fluorophore for in vivo imaging of TBI is designed. A transient hypoperfusion in the injured cerebral region, followed by fluorophore leakage, is observed. NIR‐II fluorophores can provide noninvasive assessment of TBI.